K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

30 tháng 6 2017

\(B=\dfrac{\left(x+y+z\right)^2}{x^2-\left(y^2+2yz+z^2\right)}=\dfrac{\left(x+y+z\right)^2}{x^2-\left(y+z\right)^2}\)

\(=\dfrac{\left(x+y+z\right)^2}{\left(x+y+z\right)\left(x-y-z\right)}=\dfrac{x+y+z}{x-y-z}\)

28 tháng 6 2017

Quy đồng mẫu thức nhiều phân thức

Quy đồng mẫu thức nhiều phân thức

11 tháng 11 2017

x2 +y2 +z2 -2xy-2zx-2yz=(x-y-z)2 -4yz=(x-y-z)2 - \(2.\sqrt{yz^2}\)=\(\left(x-y-z-2\sqrt{yz}\right)+\left(x-y-z+2\sqrt{yz}\right)\)

x2 -2xy - y2 -z2 =(x-y)2 -z2 =(x-y-z)(x-y+z)

9 tháng 12 2018

\(\frac{x^2+y^2+z^2-2xy+2xz-2yz}{x^2-2xy+y^2-z^2}\)

\(=\frac{\left(x-y+z\right)^2}{\left(x-y\right)^2-z^2}\)

\(=\frac{\left(x-y+z\right)^2}{\left(x-y-z\right)\left(x-y+z\right)}\)

\(=\frac{x-y+z}{x-y-z}\)

\(\dfrac{x^2+y^2+z^2-2xy+2xz-2yz}{x^2-2xy+y^2-z^2}\)

\(=\dfrac{\left(-x+y-z\right)^2}{\left(x-y\right)^2-z^2}\)

\(=\dfrac{\left[-\left(x-y+z\right)\right]^2}{\left(x-y-z\right)\left(x-y+z\right)}\)

\(=\dfrac{x-y+z}{x-y-z}\)

7 tháng 12 2018

\(\frac{x^2+y^2+z^2-2xy-2yz+2zx}{x^2-2xy+y^2-z^2}=\frac{\left(x-y+z\right)^2}{\left(x-y\right)^2-z^2}=\frac{\left(x-y+z\right)^2}{\left(x-y-z\right)\left(x-y+z\right)}=\frac{x-y+z}{x-y-z}\)